The Effect of Authentic Leadership on Creativity: the Multiple Mediating Effection of Psychological Safety and Cooperation Behavior - Woo-Su Choi(최우수); Sang-Jin Oh(오상진) (한국콘텐츠학회 논문지, 21(1), 2021)
The purpose of this study is to demonstrate the effects of authentic leadership on creativity, psychological safety, and the mediating effects of cooperative behavior in order to enhance the creativity of personnel as a means of innovation in enterprises. The hypothesis was established based on the theory and prior study of authentic leadership, creativity, psychological safety, cooperation behavior. The data collected from 353 employees of domestic enterprises were verified for reliability and validity through CFA, SPSS 25, and AMOS 25. Macro Process 3.0 was used for hypothesis testing. Verification of the hypothesis of the study model showed that authentic leadership had a significant positive effect on psychological safety, cooperation behavior and creativity, and that the mediating effect of psychological safety and cooperation behavior was also significant. The significance of this study can be found in the fact that the impact of authentic leadership has been verified based on motivation among the CMC (Componential Model of Creativity) and that it has suggested that creativity of an organization's personnel may be enhanced by changing organizational culture through leadership. KCI Citation Count: 0